2021
DOI: 10.1101/2021.10.03.462896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug screening at single-organoid resolution via bioprinting and interferometry

Abstract: There is increasing interest in leveraging tumor organoids for high-throughput drug screenings to investigate tumor biology and identify therapeutic leads. However, functional precision medicine platforms are limited by the difficulties of creating, scaling, and analyzing physiological disease models. Most systems use manually seeded organoids and take advantage of destructive endpoint assays to rapidly characterize response to treatment. These approaches fail to capture transitory changes and intra-sample het… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 104 publications
0
9
0
1
Order By: Relevance
“…Technical challenges to rapid and high-throughput screening of 3D organoids have been addressed in recent years and surpassed by different means, including alternative plate design or seeding geometries 15,150,151 .…”
Section: Drug Discovery and Development Studiesmentioning
confidence: 99%
“…Technical challenges to rapid and high-throughput screening of 3D organoids have been addressed in recent years and surpassed by different means, including alternative plate design or seeding geometries 15,150,151 .…”
Section: Drug Discovery and Development Studiesmentioning
confidence: 99%
“…We can leverage this system to screen several tens ( Figure 5 ) to hundreds of compounds 23,24 and interrogate a broad range of biological pathways 24 . Given the heterogenous cellular composition of cNFs, it will be important to incorporate assays that distinguish cell types so to determine the effects that drugs have on each distinct population 45,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the established growth conditions, we determine feasibility to perform medium-to high-throughput drug screening on cNF benign tumor organoids. Using our established organoid screening paradigm and mini-ring platform [23][24][25]45 , we tested n=43 targeted kinase inhibitors on cNF organoids established from two patients (Figure 5). NF0009 were tested in StemPro with cytokines while NF0012 was tested in StemPro with cytokines and forskolin.…”
Section: High-throughput Drug Sensitivity Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that the method could 346 effectively detect quality errors during 3D bioprinting, and a bigger error signified that a higher detection accuracy was reached. Tebon et al [ 91 ] utilized a conventional neural network to detect high-throughput drug screening problems in 3D-bioprinted organs. A quantitative phase imaging technology was employed to obtain relevant images.…”
Section: Defect Detection During 3d Bioprintingmentioning
confidence: 99%